2007
DOI: 10.1111/j.1748-5827.2006.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosis of tarsometatarsal luxations using external fixation

Abstract: This report evaluates the suitability of using an external fixator as the sole means of correcting tarsometatarsal luxations. Four dogs were included in this report. Each dog weighed more than 20 kg and had sustained a tarsometatarsal luxation with plantar, medial or lateral instability. The luxations were immobilised with an external fixator for between 12 and 17 weeks. The surgery did not involve soft tissue dissection, debridement of articular cartilage or a cancellous bone graft and no external coaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Primary ligament repair or prosthetic ligament placement may be unfeasible when there is significant soft tissue loss or extensive damage, and furthermore, it can be challenging in the cat due to its small size. Wound management is inconvenient with external coaptation; it is usually poorly tolerated in feline patients and it can lead to significant morbidity in the form of pressure sores (6,7). Arthrodesis is used as a salvage procedure once other methods of stabilisation have failed (8).…”
Section: Introductionmentioning
confidence: 99%
“…Primary ligament repair or prosthetic ligament placement may be unfeasible when there is significant soft tissue loss or extensive damage, and furthermore, it can be challenging in the cat due to its small size. Wound management is inconvenient with external coaptation; it is usually poorly tolerated in feline patients and it can lead to significant morbidity in the form of pressure sores (6,7). Arthrodesis is used as a salvage procedure once other methods of stabilisation have failed (8).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, intertarsal and tarsometatarsal joints were not exposed for arthrodesis, and no procedure for a complete osseous union was performed in these joints, as there was no significant instability and no soft tissue injury in the intertarsal and tarsometatarsal area. A previous study reported that joint ankyloses using ESF without joint exposure was very effective in stabilising the tarsometatarsal luxation by joint capsule shortening, proliferation, increased cross-linking of collagen fibrils in periarticular connective tissue, and articular cartilage atrophy [11]. Based on this report, we expected that these low-motion joints, including the intertarsal and tarsometatarsal joints, could stabilise by joint ankylosis, resulting in increased strength of the periarticular soft tissue structure, not by osseous union.…”
mentioning
confidence: 72%
“…In small animals with tarsal instability, ESF has been used for temporary immobilisation of unstable tarsal joints or rigid fixation in arthrodesis [8][9][10][11][12][13][14][15]. While ESF is a well-documented, preferred joint immobilisation technique for the temporary stabilisation of tarsocrural instability [12,14,15], its application for tarsocrural arthrodesis has rarely been reported and has only had limited use in joints with severe soft tissue injury requiring constant management of an open wound [10,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Successful use of internal and external fixation techniques to stabilize tarsal fractures and luxations in small animals have been reported (3,5,7,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). However, there have been few reports that solely assess the management of tarsal joint luxations with TESF in cats (3,21).…”
Section: Discussionmentioning
confidence: 99%
“…This process is reported to occur by proliferation of the synovial intima adhering to the cartilage, and increase in cross-linked collagen fibrils in periarticular connective tissue (13). These post-traumatic changes result in a remarkable loss in range of motion and a variable degree of degenerative changes in the joint in most of the cases in long-term follow-up (7,24). In the present study, four talo-crural luxations were managed with 24-30 day duration joint stabilization and all healed clinically well.…”
Section: Discussionmentioning
confidence: 99%